PARS processing, activity, relationships, self - University of North Carolina at Greensboro. Dept. of Counseling and Educational Development; Insight Media (firm) (Greensboro, N.C. : Dept. of Counseling and Educational Development, University of North Carolina at Greensboro ; New York : Distributed by Insight Media, 2006)
This DVD presents a model for training group facilitators to develop process skills that can be used in facilitating groups of any kind, including experiential education groups, workgroups, teams, and group counseling sessions
Title from title screen
Group facilitator: Scott Glass
Keywords: Group counseling; Counselors -- Training of